2020
DOI: 10.1109/access.2020.2998463
|View full text |Cite
|
Sign up to set email alerts
|

Process-Quality Evaluation for Wire Bonding With Multiple Gold Wires

Abstract: Taiwan is a world-leader in wafer foundry services and IC packaging and testing. Wire bonding is a crucial process in the overall IC-packaging industry chain. Thus, this paper proposes a processquality evaluation model for wire bonding with multiple gold wires. We chose process quality indices as a tool of evaluation fully mirroring process yield and quality levels. These indices contain unknown parameters and thus require sample data to estimate. We first derived the uniformly minimum variance unbiased estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Capacity analysis is more precisely summarized in indices and techniques that are used to measure, recognize uncertainty, and report the system's process capability and performance. For the past two decades, process capacity analysis has been used in a wide range of industries and organizations, including defining process requirements for new products, vendor selection, predicting a process' ability to hold tolerance, formulating quality assurance plans, and assisting designers in selecting and adjusting processes and maintaining product quality [2], [18]- [23].…”
Section: Volume … 2021mentioning
confidence: 99%
See 2 more Smart Citations
“…Capacity analysis is more precisely summarized in indices and techniques that are used to measure, recognize uncertainty, and report the system's process capability and performance. For the past two decades, process capacity analysis has been used in a wide range of industries and organizations, including defining process requirements for new products, vendor selection, predicting a process' ability to hold tolerance, formulating quality assurance plans, and assisting designers in selecting and adjusting processes and maintaining product quality [2], [18]- [23].…”
Section: Volume … 2021mentioning
confidence: 99%
“…Finally the forth way for estimator yield process by the information control chart as shown at Eq (17). All cases can be arranged as follows: (18) All cases estimation focused on keep track of yield process and the gap between the process's mean change and the target value at all times.…”
Section: B Estimation For Ssy Actual Yield Based On 6σmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a large number of studies have also suggested that the radar chart is a visual 2D plan, which is a practical graphical analysis and management tool with high readability and a wide range of applications, including engineering, education, management, etc. [19][20][21][22][23][24][25][26][27]. The radar chart can evaluate the performance of all workstations at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Gold wire bonding is the most commonly used technology to interconnect chips with low cost in microelectronics packaging. Since its invention in the 1960s, wire bonding has evolved into a dominant form of first-level chip or circuit interconnect with a large number of fixed user groups and equipment reserves [6][7][8][9][10][11][12][13]. Threedimensional stacked packaging through large-span-ratio and high-density wire bonding can maximize chip integration, boost the device performance, reduce the device size, and shorten the development cycle, which will further ensure a smooth transition of interconnect technology in the Post Moore Era [14].…”
Section: Introductionmentioning
confidence: 99%